Diane (Privateer) records - Diane (Privateer)
Volume containing documents relating to outfitting costs, crew wages, profits from prizes, and other financial matters; instructions to captains; and orders for a cruise against the British. Also includes a sale notice for the British merchant vessel Appleton that was captured by the Diane.
French privateer, also known as La Diane, owned by Jean Forestier, under the command of Georges Mathieu Forestier, and ported in Bayonne, France.
Collection material in French.
Keywords: Forestier, Georges Mathieu; Forestier, Jean, -- active 1746.; Appleton (Ship); Privateering -- France; Bayonne (France) -- Harbor; France -- History, Naval; Great Britain -- History, Naval